2015
DOI: 10.1590/2175-7860201566218
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Phylogenetic Analysis of Two Early-Diverging Genera of Bromelioideae (Bromeliaceae)

Abstract: Bromelia includes 66 species, grouped in three subgenera: Bromelia, Distiacanthus and Karatas. The genus is one of the earlier divergent groups within Bromelioideae, a subfamily with innumerable problems of generic delimitation. Considering that few phylogenetic studies have included more than one species of Bromelia, the objectives of this study were to carry out a phylogenetic analysis for the genus, seeking to evaluate its monophyly as well as its subgenera, and to better understand the interspecific evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
(68 reference statements)
0
12
0
2
Order By: Relevance
“…() for relationships within Orthophytum , Monteiro et al . () for relationships within Bromelia , and Cruz et al . () for relationships within Cryptanthus .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…() for relationships within Orthophytum , Monteiro et al . () for relationships within Bromelia , and Cruz et al . () for relationships within Cryptanthus .…”
Section: Methodsmentioning
confidence: 97%
“…For Pitcairnia, the tree used here was based on the morphological phylogeny of Saraiva et al (2015) and included 56 terminal taxa. For the terrestrial Bromelioideae, a composite tree was produced based on molecular phylogenetic analyses, using information from Givnish et al (2011) and Silvestro et al (2014) for intergeneric relationships, from Louzada et al (2014) for relationships within Orthophytum, Monteiro et al (2015) for relationships within Bromelia, and Cruz et al (2017) for relationships within Cryptanthus. It included 111 terminal taxa including a tip for the Core Bromelioideae.…”
Section: Taxon Sampling and Leaf Shape Categorization-the Genusmentioning
confidence: 99%
“…Asimismo, se presentan brácteas del pedúnculo durante la antesis, brácteas florales iguales o superiores al ovario, y no presentan sépalos. Las flores poseen pétalos carnosos, crecen en grupo en un eje corto y los pétalos miden alrededor de 3 cm (Espejo-Serna et al, 2004;Monteiro et al, 2015).…”
Section: Descripción Botánica De Plantas De Bromeliaunclassified
“…Gilmartin & Brown, 1987;Varadarajan & Gilmartin, 1988). The use of morphological data in phylogenetic analysis decreased for many years before being re-established in the last decade, when micro-and macromorphological traits began to be employed at inter-and infrageneric levels (De Faria et al, 2004;Hornung-Leoni & Sosa, 2008;Almeida et al, 2009;Aguirre-Santoro et al, 2015;Da Costa et al, 2015;Donad ıo, Pozner & Giussani, 2015;Monteiro, Mantovani & Forzza, 2015;Saraiva, Mantovani & Forzza, 2015) and some studies in recent years have identified morphological characters with good taxonomic value for phylogenetic inferences (e.g. Versieux et al, 2010;De Faria, Vieira & Wendt, 2012;Magalhães & Mariath, 2012;Santos-Silva et al, 2013;Nogueira et al, 2015).…”
Section: Evolution and Phylogeneticsmentioning
confidence: 99%